Spur cell anaemia and hepatic iron stores in patients with alcoholic liver disease undergoing orthotopic liver transplantation. Issue 2 (1st August 1999) - Pascoe, A; Kerlin, P; Steadman, C; Clouston, A; Jones, D; Powell, L; Jazwinska, E; Lynch, S; Strong, R
Abstract : BACKGROUND: Following orthotopic liver transplantation (OLT) histological examination of explant livers from patients with alcoholic liver disease (ALD) sometimes shows extensive iron deposits in a distribution suggestive of homozygous haemochromatosis. AIMS: To use haemochromatosis gene (HFE) assays to distinguish between ALD with notable siderosis and hereditary haemochromatosis. To evaluate the possible influence of spur cell haemolytic anaemia on hepatic iron loading. PATIENTS: Thirty seven patients with ALD were abstinent for at least six months prior to OLT. Twenty three patients had transferrin saturations greater than 55%, 16 also had increased serum ferritin (>350 μg/l). Eight of 37 (22%) explant livers had grade 3 or 4 hepatic iron deposition, predominantly in hepatocytes. Of these, four had a hepatic iron index greater than 1.9 and most seemed to have spur cell haemolytic anaemia. METHODS: Mutation analysis for C282Y and H63D mutations was performed on DNA extracts from peripheral blood or explant liver. Spur cell haemolytic anaemia was diagnosed when the haemoglobin was 105 g/l in the presence of notable acanthocytosis. RESULTS: None of the eight patients with grade 3 or 4 hepatic iron had evidence of the C282Y mutation. Two of the eight were heterozygous for H63D. None of the remaining 28 patients tested showed homozygous HFE mutations. Spur cell anaemia was present in six of the eight patients with heavy iron deposition and only one of the remaining patients. CONCLUSIONS: The HFE mutation was not present in these patients with advanced ALD and heavy iron loading. Spur cell haemolytic anaemia provides an alternative potential mechanism for the heavy iron loading.